The Rise in Female Participation in Colombia: Children, Education or Marital Status - Amador, Diego (Washington, DC: World Bank, 2012)
Colombia has experienced a secular increase in female labor participation, which passed from nearly 47% in 1984 to 65% in 2006. We decompose the evolution of participation into changes in the composition of the population and changes in the participation rates by groups (defined according to the variables that appear most relevant: educational attainment, fertility and marital status). The increase in participation is driven by the increase in the participation rate of women who were married or cohabiting and women with low educational attainment. Fertility status appears less important. Changes in composition are second order effects. When exploring the factors behind the observed changes, we find that the increase in participation is associated to cultural and perception changes (namely, past participation and divorce rates), and to a small degree to changes in legislation. We find no evidence that the increase in participation is correlated with the business cycle. Keywords: Gender, Labor Force Participation, Colombia JEL Codes: J16, J21